Beyond Translation: Clarity, Sensitivity, and Artistry in Benedict Anderson’s Reading of Indonesian Literature - Novita Dewi (Lingua Cultura, 2018)
This research was to reconfirm Anderson’s theory (and praxis) of translation, i.e., transfer of language and culture from one to another with clarity, sensitivity, and high artistry. The analytical method used the application of diverse translation strategies to achieve pragmatic equivalence, i.e., the use of footnotes and foreignization-domestication principles. To consolidate the discussion, this research examined closely Anderson’s English translation of part of Titie Said’s “Bidadari” in his analysis of the novel and his translation of Pramoedya Ananta Toer’s short story “Nyonya Dokter Hewan Suharko”. The results indicate that what appears in his translation work is a broad range of discourses that help expound foreign-language (in this case English) intelligibility from the translating (Indonesian) one. His treatment of domesticating and the foreignizing translation is critically done owing to his gift of interests, passion, and persistence in the subject.